The Art of Knowledge Exchange : A Results-Focused Planning Guide for Development Practitioners in the Social, Urban, Land, and Resilience Sectors - Kumar, Shobha; Leonard, Aaron; Watkins, Ryan; Vovides, Yianna; Kerby, Brigitte (World Bank, Washington, DC, 2018)
Based on the original Art of Knowledge Exchange: A Results-Focused Planning Guide for Development Practitioners, this guide has been customized for practitioners in the urban, social, land, and resilience sectors. It offers a practical step-by-step framework with illustrative examples on how to design, implement, and measure progress with regard to knowledge exchange initiatives. While the guide contains information that is of value to all those involved in knowledge exchange from the local to the global level, it is particularly geared to those who broker the exchange of knowledge and expertise on development challenges and solutions in the areas of urban and social development, land administration, and resilience.